Defect‐Engineered Dzyaloshinskii–Moriya Interaction and Electric‐Field‐Switchable Topological Spin Texture in SrRuO3 (Adv. Mater. 33/2021). Issue 33 (17th August 2021) - Lu, Jingdi; Si, Liang; Zhang, Qinghua; Tian, Chengfeng; Liu, Xin; Song, Chuangye; Dong, Shouzhe; Wang, Jie; Cheng, Sheng; Qu, Lili; Zhang, Kexuan; Shi, Youguo; et al.
Abstract : Skyrmionic Bubbles In article number 2102525, Lingfei Wang, Jinxing Zhang, and co‐workers report that, at the interface between the perovskite‐structured SrTiO3 (001) substrate and SrRuO3 thin film, the distinct chemical potentials make the oxygen vacancies preferentially diffuse from SrTiO3 to SrRuO3 . This unidirectional oxygen‐vacancy diffusion process can create a new interface between stoichiometric and oxygen‐deficient SrRuO3 layers, and the resultant inversion‐symmetry‐breaking can further trigger a vortex‐like spin texture, namely, skyrmionic magnetic bubbles.